2019
DOI: 10.4103/ijo.ijo_1854_18
|View full text |Cite
|
Sign up to set email alerts
|

Rotation versus non-rotation of intraocular lens for prevention of posterior capsular opacification

Abstract: Purpose: To study the effect of rotation of intraocular lens (IOL) on posterior capsular opacification (PCO) in eyes with phacoemulsification. Methods: This was a prospective, comparative, randomized case series. One eye of each patient was randomized to one of two groups. The 360-degree rotation of IOL was carried out after its placement in the capsular bag (rotation group). The control group had no rotation of IOL. PCO was analyzed by an independent observer on EPCO c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In spite of this, the technique's usefulness should be evaluated in light of the possibility of PCO development and the availability of Nd: YAG capsulotomy. 25 After Nd: YAG posterior capsulotomy was performed, Ramachandra and Kuriakose, 26 found better vision and a substantial improvement in refraction, leading them to infer that a new spectacle correction was required. The present study showed that anterior chamber depth decreased gradually from pre-laser value to the last follow-up period (3 months) with statistically highly considerable variation between the two periods (p <0.001), while the central macular thickness is markedly elevated after laser, then decreased gradually till the end of the follow-up period with statistically highly significant value between the two periods (p <0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, the technique's usefulness should be evaluated in light of the possibility of PCO development and the availability of Nd: YAG capsulotomy. 25 After Nd: YAG posterior capsulotomy was performed, Ramachandra and Kuriakose, 26 found better vision and a substantial improvement in refraction, leading them to infer that a new spectacle correction was required. The present study showed that anterior chamber depth decreased gradually from pre-laser value to the last follow-up period (3 months) with statistically highly considerable variation between the two periods (p <0.001), while the central macular thickness is markedly elevated after laser, then decreased gradually till the end of the follow-up period with statistically highly significant value between the two periods (p <0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The IOL implanted under BSS undergoes rotation in the bag that can mechanically remove LECs. Joshi et al ,[ 9 ] in their study on rotation versus nonrotation of IOL, showed a decreased ND: YAG capsulotomy rate in the rotation group in the follow-up period of 24 months. However, they rotated the IOL by 360°.…”
Section: Discussionmentioning
confidence: 99%
“…Various modalities are available for preventing PCO, such as effective hydrodissection, cortical cleanup, equatorial epithelial lens fiber removal,[ 3 ] sealed-capsule irrig ation,[ 4 ] square-edged optic of the IOL,[ 5 6 ] ultraviolet treatment of lens epithelial cells (LECs),[ 7 ] trypan blue dye irrigation in the capsular bag,[ 8 ] and IOL rotation in the capsular bag. [ 9 ]…”
mentioning
confidence: 99%
“…Joshi et al, assessed the effect of rotation of the implanted lens/IOL by 360 • during cataract phacoemulsification [80]. After placing/inserting the lens/IOL in the capsule, the lens was rotated 90 • using a Sinskey hook inserted through the corneal incision.…”
Section: Clinical Trialsmentioning
confidence: 99%